PERBANDINGAN KINERJA BANK SWASTA DI INDONESIA BERDASARKAN PEMENUHAN MODAL MINIMUM - Erfan Herwinanto (Jurnal Riset Akuntansi dan Keuangan, 2015)
This study aims at revealing the bank capital influence its operational activities. This study employssecondary datum which is obtained from bank indonesia. From the existing data banks, 171 financialstatement of banks are used for sample from 2005 to 2007, which breakdown in 2005 consist 62, 2006consist 56, 2007 consist 53 financial statement. In order to measure banks activities, CAMELScomponent is conducted in accordance with bank indonesia regulations. Based on the analysis at allbanks on 2005-2007, it revals that KPPM component, capital component, NIM component, betweenbank and its capital below minimum and bank and its capital above, the difference is not found.Meanwhile differences are found when ROE component, BOPO component and LDR component,between bank and its capital below minimum and bank its capital above minimum.Keywords: minimum capital, bank activity, CAMELS